Current state and prospects of protoplast technology and potato somatic hybridization (review) - O. B. Polivanova; A. S. Egorova; A. B. Sivolapova; S. V. Goryunova (Аграрная наука Евро-Северо-Востока, 2023)
Wild Solanum species have often been used as sources of important agricultural traits, including resistance to various diseases, pests, and abiotic factors. However, their large-scale use in potato breeding is limited by complex barriers of sexual incompatibility with Solanum tuberosum. Fusion of protoplasts enzymatically isolated from somatic cells is one of the approaches to overcoming sexual incompatibility. The diverse nuclear and cytoplasmic traits exhibited by potato somatic hybrids provide new genetic material for breeding programs, which is confirmed by the creation of a large number of somatic hybrids of cultivated potatoes with wild Solanum species. The research in development of somatic potato hybrids by means of protoplast fusion has been carried out for more than 40 years already. In this review, the prospects for the use of this technology in modern potato breeding are considered. Genomic, transcriptomic, and proteomic studies provide further insight into the fundamental processes underlying the somatic hybrids formation, such as cell wall formation, chromosomal rearrangements in fusion products, regeneration, and also make a significant contribution to understanding the processes of genome stabilization. Improvement in the methods of molecular screening of both genome and cytoplasm also contributes to the expansion of the field of application of somatic hybrids in breeding. Finally, it has been shown that somatic hybridization promotes the introgression of important agricultural traits, primarily resistance to pathogens.